Impact of Covid-19 pandemic on injection-based practice: report from an Italian multicenter and multidisciplinary survey - Tenti, S.; Mondanelli, N.; Bernetti, A.; Mangone, M.; Agostini, F.; Capassoni, M.; Cheleschi, S.; De Chiara, R.; Farì, G.; Frizziero, A.; Giannotti, S.; Guiducci, S.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. There are no papers exploring the impact of COVID-19 pandemic on the injection-based practice in patients affected by different rheumatic diseases, including osteoarthritis. The aim was to investigate the impact of COVID-19 pandemic on injection-based practice trough the Italian country.Study design. A survey-based retrospective cross-sectional studyMethods. An Italian-language questionnaire was developed by a group of senior researchers and distributed by e-mail to some Rheumatology, Orthopedic and Rehabilitation Units from different geographic areas of Italy. The survey included information about the number of injections performed during COVID-19 pandemic (stratified by injected agents and injected joint), in comparison to the pre-pandemic period, and the possible reasons behind an eventual reduction. Responses were collected and descriptive analysis calculated.Results. Eleven centers of the National Health Service completed the survey. The activities of the injections services significantly decreased across the country with a percentage of reduction of 60% compared to the pre-pandemic period. A significant reduction of both intra-articular and peri-articular injections was registered. Among intra-articular. treatments, the most affected ones were the hyaluronic acid injections, when compared to corticosteroids. A significant decrease of the total amount of peri-articular injections was observed. The strict government restrictions and the fear of patients to become infected represented the most limiting factors.Conclusions. The reported decrease of the injection-based practice in our country during the COVID-19 pandemic highlights the detrimental effects of the COVID-19 pandemic on the management of chronic musculoskeletal diseases with possible negative consequences in terms of disability and quality of life.